A review of reliability tests on safety technologies - Mohammad Hisyammuden, Muhammad Syahmi; Hassan, Suhaimi; Mustaffa, Musfirah; Jumari, Mohamad Zhairul Iqumal; Mat Nadir, Mohamad Amirul; Yusof, N. M.; Ikhsan, M. S.; Ismon, Maznan; Zakaria, Hanis; Marwah, Omar Mohd Faizan; Yusof, M. S.; Nik Aziz, Nik Nazmi Amir; et al. (2023)
A road maintenance employee is someone who ensures that roads and highways are safe, clean, and accessible. They perform a variety of tasks that demand physical exertion, such as repairing damaged automobiles, performing routine check-up procedures, or performing restoration work, among others. As a result, these workers may be exposed to hazardous situations, as there have been multiple accidents involving highway workers on the road recently. Signal Warning Detector casing structure was designed as part of a safety system to provide early warning to highway workers as traffic accidents among highway workers have become a concern. This study reviews the different reliability tests done on casing structure by previous researchers. Therefore, this study applies laboratory experiments to further test the reliability for the SWAD transmitter and receiver casing structure as a development step towards producing a reliable SWAD system